MANAGEMENT OF BERINGIN JAYA VILLAGE ASSETS IN LIVING DISTRICT IN KUANTAN SINGINGI DISTRICT - Agung Supriyanto; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Good management of village assets is based on applicable regulations and has guidelines in their management. Village asset management is one way for villages to be able to carry out a development. Village asset management is one way for villages to be able to carry out a development in good management, of course using guidelines in its management, management itself is a series of activities ranging from planning, procurement, utilization, maintenance, administration and deletion. The purpose of this study is the Asset Management in Beringin Jaya Village, Singingi Hilir Subdistrict, Kuantan Singingi Regency and to find out the inhibiting factors of Beringin Jaya Village Asset Management in Singingi Hilir Subdistrict, Kuantan Singingi District. The theoretical concept used by the author is Village Asset Management. . In collecting data, the writer uses interview and observation techniques. The author uses the informant as a source of information as a source in the validity of the data. The results of this research indicate that the Beringin Jaya Village Asset Management in Singingi Hilir District, Kuantan Singingi Regency, shows that in the management of village assets in implementation there is still a lack of village asset data found in the asset inventory and found development assets that require renovation. The inhibiting factors of Asingin Jaya Village Asset Management in Singingi Hilir Subdistrict, Kuantan Singingi Regency include human resources and facilities and infrastructure.Keywords: Village Asset Management